Healthy Eating Culture in a Valeological Approach: Theory, Practice and Innovative Methods (Novateur Publications, 2025)
The monograph "Healthy Eating Culture in a Valeological Approach: Theory, Practice and Innovative Methods" explores the interconnection between nutrition, health, and valeology — the science of healthy living. Integrating theoretical foundations with practical applications, the work presents a comprehensive analysis of how dietary habits influence physical and psychological well-being. Special attention is given to the development of a healthy eating culture as a preventive tool against chronic diseases and lifestyle disorders. The authors offer evidence-based recommendations, emphasizing personalized nutrition, food literacy, and socio-cultural factors shaping eating behavior. Innovative educational and methodological approaches are also introduced to enhance health promotion strategies across various populations. This monograph is intended for researchers, educators, healthcare professionals, and students interested in nutrition science, preventive medicine, and health education. It serves as both a theoretical guide and practical resource for fostering a holistic and sustainable model of healthy eating in alignment with modern valeological principles.